Serum alkaline ribonuclease derived from vascular endothelial cells is raised in patients with rheumatoid vasculitis. Issue 11 (November 1986) - Oribe, M; Shingu, M; Nobunaga, M
Abstract : We investigated the mechanisms of the marked increase of alkaline ribonuclease (RNase) in the sera of patients with rheumatoid arthritis associated with vasculitis. Among various tissues examined, blood vessels contained higher levels of alkaline RNase than acid RNase. Cultured human endothelial cells contained significantly higher amounts of alkaline RNase than acid RNase. In contrast, acid RNase was predominant in most other tissues and cells. Endothelial cells cultured with sera from patients with vasculitis released alkaline RNase into the extracellular medium. The phosphocellulose chromatographic profile of these sera differed from that of sera from healthy subjects. These results imply that the alkaline RNase in sera of patients with vasculitis is derived from blood vessels, probably from endothelial cells.